Intensification of Waste Valorization Techniques for Biogas Production on the Example of Clarias gariepinus Droppings - Vladimir Shtepa; Magdalena Balintova; Aliaksei Shykunets; Yelizaveta Chernysh; Viktoriia Chubur; Leonid Plyatsuk; Natalia Junakova (Fermentation, 2023)
This study aims to evaluate the process of biogas production from the droppings of Clarias gariepinus under intensification of methanogenesis using electrolysis pretreatment and electro-fermentation in comparison with the addition of stimulating substances (humates and zeolites). For the realization of a series of experiments, laboratory installations of electrolysis and electro-fermentation were developed. The following parameters were monitored: biogas composition, chemical oxygen demand, redox potential, hydrogen potential, nitrates, ammonia–ammonium, and nitrites. A taxonomic classification and review of the metabolic pathways were performed using the KEGG, MetaCyc, and EzTaxon databases. The stimulation of biomethanogenesis in the utilization of catfish droppings by the introduction of additional electron donors—exogenous hydrogen (electro-fermentation)—was confirmed. The electro-fermentation process released 4.3 times more methane compared to conventional conditions and stimulant additives and released 1.7 times more with electrolysis pretreatment. The main metabolic pathways of electron acceptor recruitment using bioinformatic databases are highlighted, and models of CO2 transformation involving exogenous hydrogen along the chain of metabolic reactions of methanogenesis are generated. The summary model of metabolic pathways of methanogenesis are also proposed. Based on the results of the present and previous studies, two technological solutions are proposed to implement the process of anaerobic treatment intensification of excreta of the clariid catfish. Additional studies should include the optimization of the operation mode of electro-fermentation and electrolysis pretreatment of the substrate during the aquacultivation process.